(untitled) (Research, Society and Development, 2022)
Osteoporosis is an osteometabolic pathology, characterized by calcium deficit and deformation of bone microstructure and susceptibility to fractures. With the greater aging of the population, genetic predisposition, the predominance of females and the use of certain drugs, this finding has greatly increased its incidence and characterizes a potential risk to the population. The following article aimed to describe the main clinical considerations of osteoporosis for public health. This is a narrative review of literature based on SciELO, PubMed, LILACS, Reasearch, Society and Development and Google Scholar platforms in the time frame from 2002 to 2022, using the following descriptors: bone; calcium deficit; osteoporosis. Osteoporosis is an osteometabolic disease that has several classifications, numerous etiologies, a clinical picture that depends on the intensity, extent and degree of involvement. It is essential to carry out the identification of each of these determinants to properly conduct the patient’s therapy in order to promote quality of life, disease prevention and basic remission rates. There is a lot of information relevant to the topic in the scientific literature, so it is essential for health professionals and the community to be informed about the topic and to be alert to suspicion and ideal early conduct to promote the improvement of public health.